Megafauna do quaternário tardio dos depósitos cársticos do Alto Vale do Ribeira, sudeste do Estado de São Paulo, Brasil - Ghilardi, Aline Marcele (2011)
The carbonate caves of the Upper Ribeira Valley, southeastern São Paulo State, Brazil, preserve abundant fossil record of Pleistocene-Holocene South American megafauna. This work presents a historical review of its paleontological studies, as well as an update taxonomic survey of the megafauna material gathered since the beginning of the explorations in the area. Herein are also discussed paleobiogeographic and paleoecological questions and presented new Electron Spin Resonance dating results of the Ribeira s material. The fossil megafauna of the Upper Ribeira karstic region include: Eremotherium laurillardi, Nothrotherium maquinense, Lestodon armatus, Catonyx cuvieri, Ocnopus gracilis‟, Ahytherium aff. aureum, Glyptodon clavipes, G. reticulatus, Hoplophorus cf., Toxodon spp., Stegomastodon waringi, Tapirus terrestris,. Equidae indet., Smilodon populator and Panthera onca, of which only P. onca and T. terrestris still remain in the region. The register of Equidae here presented is the first for this area and also the first formal entry for the São Paulo state. The fossil assemblage recorded shows greater biogeographical affinity to the mega-mammal community of the intertropical region, though a typical taxon from pampean localities was also found. This denotes that the area should be a transition zone. The ecology of the species found suggests bygone occurrence of fairly different environmental settings than the existing one in the area. There were more temperate climates associated with open vegetation physiognomies, what agrees with the already known paleopalinological data. The fossil material does not show any kind of cronocorrelation given the type of genesis of the cave accumulations; and paleoecological investigations indicate that these fossils does not represent a real biocoenosis, but depict different faunistic moments related to climate oscillations during the Quaternary. The results obtained with the absolute dating corroborate the hypothesis that the Vale do Ribeira material belong to Late Pleistocene Holocene age; and also give the first biocronological insight for an extinct group in this area. To better understand the information provided by these deposits, further efforts on prospection and dating should be conducted, as well as detailed taphonomic investigations. The studies of the Quaternary fauna in São Paulo State come to fill an important gap in the intricate history of the South American megafauna.